Traversing the Wasteland: A Framework for Assessing Ecological Threats to Drylands. (18th December 2019) - Hoover, David L; Bestelmeyer, Brandon; Grimm, Nancy B; Huxman, Travis E; Reed, Sasha C; Sala, Osvaldo; Seastedt, Timothy R; Wilmer, Hailey; Ferrenberg, Scott
Abstract: Drylands cover 41% of the Earth's terrestrial surface, play a critical role in global ecosystem function, and are home to over two billion people. Like other biomes, drylands face increasing pressure from global change, but many of these ecosystems are close to tipping points, which, if crossed, can lead to abrupt transitions and persistent degraded states. Their limited but variable precipitation, low soil fertility, and low productivity have given rise to a perception that drylands are wastelands, needing societal intervention to bring value to them. Negative perceptions of drylands synergistically combine with conflicting sociocultural values regarding what constitutes a threat to these ecosystems. In the present article, we propose a framework for assessing threats to dryland ecosystems and suggest we must also combat the negative perceptions of drylands in order to preserve the ecosystem services that they offer.